Effectiveness Evaluation of Insecticides Containing Spirotetramat + Abamectin Active Ingredients Against Thrips (Thrips palmi) in Tomato Plants - Fitriyah, Vebriyanti; Rachmawati, Rina; Widjayanti, Tita (University of Brawijaya, 2025)
The tomato plant (Lycopersicum esculentum Mill.) is one of the horticultural crops that is frequently cultivated and consumed due to its considerable nutritional value, including vitamins A and C. In the cultivation process, farmers often face problems caused by plant pests, one of which is Thrips (Thrips palmi Karny). This study aims to determine the effectiveness of insecticides containing the active ingredients spirotetramat + abamectin at several concentrations against T. palmi. Research activities were conducted in Pujon District, Malang Regency, and Junrejo District, Batu City, East Java, from April to June 2023. The research used a Randomized Complete Block Design (RCBD) with 5 treatments: spirotetramat + abamectin 1.00 ml/l; 0.75 ml/l; 0.50 ml/l; 0.25 ml/l; and a control. The results showed that the use of spirotetramat + abamectin insecticides at different concentrations affected the average T. palmi population level and yield in tomato plants. Treatment with a concentration of 1.00 ml/l was the most effective, achieving an efficacy index (EI) value of more than 70%.